Factors Influencing Leukocyte Adherence in Microvessels - Harvey, Mayrovttz N.; Mary, Wiedeman P.; Tuma, Ronald F. (Thrombosis and Haemostasis, 1977)
In vivo studies of the microcirculation of an untraumatized and unanesthetized animal preparation has shown that leukocyte adherence to vascular endothelium is an extremely rare occurrence. Induction of leukocyte adherence can be produced in a variety of ways including direct trauma to the vessels, remote tissue injury via laser irradiation, and denuding the epithelium overlying the observed vessels. The role of blood flow and local hemodynamics on the leukocyte adherence process is quite complex and still not fully understood. From the results reported it may be concluded that blood flow stasis will not produce leukocyte adherence but will augment pre-existing adherence. Studies using 2 quantitative measures of adherence, leukocyte flux and leukocyte velocity have shown these parameters to be affected differently by local hemodynamics. Initial adherence appears to be critically dependent on the magnitude of the blood shear stress at the vessel wall as evidenced by the lack of observable leukocyte flux above some threshold value. Subsequent behavior of the leukocytes as characterized by their average rolling velocity shows no apparent relationship to shear stress but, for low velocities, may be related to the linear blood velocity.